The effect of pentanol addition on the particulate emission characteristics of a biodiesel operated diesel engine. (1st December 2017) - Yang, Ke; Wei, Long; Cheung, C.S.; Tang, Chenglong; Huang, Zuohua
Highlights: Blending pentanol with biodiesel retarded the start of combustion and shortened the combustion duration. The BP blends reduced the counts of particles in all size groups. They reduced EC emissions but increased OC fractions. They reduced almost all the individual particle-phase PAHs and also carcinogenic potential. Abstract: In the present study, combustion performance and the physical and chemical characteristics of soot particles from a DI diesel engine were studied. The engine was fueled with n -pentanol mixed with biodiesel at 15% and 30% by volume and operated at 1800 rpm under three engine loads (20%, 50% and 80% load). In comparison with pure biodiesel, the pentanol-biodiesel blends lead to delayed start of combustion and shortened combustion duration. The particle number concentrations of all size groups are reduced for biodiesel-pentanol blends in all the tested conditions, due to longer ignition delay time, lower viscosity and boiling point, and higher oxygen content of pentanol. The brake specific elemental carbon (EC) emissions of biodiesel were found to be lower compared to diesel and after adding pentanol in biodiesel, the EC emissions further decrease. While for organic carbon (OC) emissions, biodiesel and diesel are at similar level under the tested engine loads, and the blends show a higher fraction of OC at low and medium engine loads. The blended fuel with higher proportion of pentanol gives lower total particle-phase PAHs emissions and also a lower benzo[a]pyrene equivalent (BaPeq ) compared to pure biodiesel under the tested engine loads.